2012
DOI: 10.1088/0004-6256/143/3/73
|View full text |Cite
|
Sign up to set email alerts
|

The Sun Was Not Born in M67

Abstract: Using the most recent proper-motion determination of the old, solar-metallicity, Galactic open cluster M67 in orbital computations in a non-axisymmetric model of the Milky Way, including a bar and three-dimensional spiral arms, we explore the possibility that the Sun once belonged to this cluster. We have performed Monte Carlo numerical simulations to generate the present-day orbital conditions of the Sun and M67, and all the parameters in the Galactic model. We compute 3.5 × 10 5 pairs of orbits Sun-M67 looki… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 112 publications
(148 reference statements)
2
70
0
Order By: Relevance
“…(We have also made experiments with modifications of the z-gradient of the potential by ±10% to explore the effects of its uncertainties.) To this we have added two stellar spiral arms, following the recipe of Pichardo et al (2003Pichardo et al ( , 2012, with a pitch angle of 15.5 degrees, a radial scale length exponential mass decrease along the arms of 3.9 kpc, a mass of 4 · 10 9 M and a constant pattern speed of 24 km/s kpc −1 . Each arm is represented numerically by 100 oblate inhomogeneous spheroids with semi-major and minor axes of 1000 pc and 500 pc respectively, and with a mutual distance between the spheroid centres of 500 pc.…”
Section: Scattering Of M 67 To Its High Altitudes: a Global Syntheticmentioning
confidence: 99%
See 3 more Smart Citations
“…(We have also made experiments with modifications of the z-gradient of the potential by ±10% to explore the effects of its uncertainties.) To this we have added two stellar spiral arms, following the recipe of Pichardo et al (2003Pichardo et al ( , 2012, with a pitch angle of 15.5 degrees, a radial scale length exponential mass decrease along the arms of 3.9 kpc, a mass of 4 · 10 9 M and a constant pattern speed of 24 km/s kpc −1 . Each arm is represented numerically by 100 oblate inhomogeneous spheroids with semi-major and minor axes of 1000 pc and 500 pc respectively, and with a mutual distance between the spheroid centres of 500 pc.…”
Section: Scattering Of M 67 To Its High Altitudes: a Global Syntheticmentioning
confidence: 99%
“…If the early M 67 really would have been the original environment of the Sun, the arguments by Pichardo et al (2012) suggest that the Sun should have been formed in the cluster when it still had an orbit much closer to the Galactic plane and diffused out of the cluster. In some latter scattering process against one or several massive objects the cluster was then accelerated into its present high altitude orbit.…”
Section: Did the Sun Originate In M 67?mentioning
confidence: 99%
See 2 more Smart Citations
“…Its age and composition are nearly indistinguishable from the Sun (Önehag et al 2011), which led some to question whether M67 was the Sun's natal cluster. However, Pichardo et al (2012) concluded that this scenario was unlikely based on a dynamical analysis of the Sun and M67's motion through a realistic Milky Way gravitational potential. Crucially, the membership and multiplicity of M67 have been carefully determined from over 40 years of radial velocity monitoring (Geller et al 2015;Latham 2007).…”
Section: M67 As a Solar Benchmarkmentioning
confidence: 99%